Verification in Results-Based Financing (RBF) : The Case of the United Kingdom - Cashin, Cheryl; Vergeer, Petra (World Bank, Washington, DC, 2013)
Paying health care providers performance based incentive payments is one form of Results-Based Financing (RBF). Verifying that providers have reached set performance thresholds is a crucial part of RBF program implementation and key to maintaining the transparency, fairness, and viability of the programs. The national health service of the United Kingdom has been implementing one of the largest RBF initiatives worldwide, the Quality and Outcomes Framework (QOF), since 2004. The QOF provides incentive payments for primary care providers to improve quality of care and patient experience. Its verification process is well developed and relies on a highly sophisticated clinical information system as the foundation for performance data. This case study describes the process for verification of achievement rates under the QOF and identifies lessons learned applicable to other RBF programs. The case study is part of a broader analysis, which includes multiple country case examples, to expand knowledge about the verification process and practices to address the immediate design and implementation needs of RBF programs.